Evaluasi Penggunaan Obat Anti diabetes Oral pada Pasien Diabetes Melitus Tipe II di Instalasi Rawat Jalan Rumah Sakit Azizah Metro - Pamungkas, Pratiwi May; Ginaris , Rifkarosita Putri; Nurrahman, Alfina (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Diabetes mellitus (DM) is a chronic metabolic disease characterized by elevated blood glucose levels (hyperglycemia). This condition arises due to impaired insulin production, the body's inability to effectively utilize insulin, or a combination of both. The rational use of antidiabetic drugs is crucial in managing blood glucose levels in diabetic patients. This study aimed to evaluate the use of oral antidiabetic drugs in patients with type 2 DM at the outpatient clinic of Azizah Metro Hospital. The research employed a descriptive design with retrospective data collection, using patient medical records from October to December 2024 as the data source. The sampling technique was total sampling, with a total of 80 patients as respondents. The majority of patients were female (77.5%), and the most prevalent age group was 56–65 years (48.75%). Most patients were on monotherapy (68.75%), with glimepiride being the most frequently prescribed drug (33.75%). The evaluation results showed that all patients (100%) met the criteria for appropriate drug use based on patient condition, indication, drug type, and dosage. In conclusion, the use of oral antidiabetic drugs in type 2 DM outpatients at Azizah Metro Hospital during the period of October–December 2024 has met the principles of rational therapy with an accuracy rate of 100%.